Antibacterial Inhibition Test Against the Combination Extract of Moringa Leaf ( Moringa oliefera ) and Basil Leaf ( Ocimum basilicum ) as a Substitute for Feed Additive - Erika Rahayu; Nancy Lahay; Jamilah (Hasanuddin Journal of Animal Science (HAJAS), 2022)
One of the efforts to increase poultry productivity is to provide feed additives that are mixed with feed. Feed additives to replace antibiotics such as probiotics, prebiotics, and acidifiers can be used as additives to feed because of their ability to regulate digestive tract conditions. Moringa leaves (Moringa oliefera) and basil leaves (Ocimum basilicum) contain active compounds that can used to inhibit the growth and extinguish Escherichia coli and Staphylococcus aureus. The purpose of this study was to determine the effectiveness of each of the bioactive substances produced from a combination of extracts of several plants which were combined to have a greater antibacterial inhibition compared to single plant extracts. The research design consisted of 5 treatments and 4 replications with treatment P0 (positive control, namely contrimexasol), P1 (Moringa leaves 55% + Basil leaves 25%), P2 (Moringa leaves 50% + basil leaves 30%), P3 (Kelor leaves 45 % + Basil leaves 35%), P4 (Moringa leaves 40% + Basil leaves 40%). The study used RAL (Completely Randomized Design) and further tests were carried out with the BNT test at 5% level to determine the difference between each replicate. The results was indicated that the highest inhibitory power was found in Gram positive bacteria and the lowest inhibitory power was found in Gram negative bacteria. The combination of Moringa leaves and Basil leaves reaches a concentration of 55% + 25% able to inhibit the growth of Gram positive bacteria and Gram negative bacteria, so that it is possible to improve the digestive system in poultry and can inhibit the bacteria that cause diarrhea. Keywords : Probiotics, bioactive substance, inhibitory power, digestive system, Staphylococcus aureus